Evaluation of imaging setups for quantitative phase contrast nanoCT of mineralized biomaterials. (25th April 2022) - Suuronen, Jussi-Petteri; Hesse, Bernhard; Langer, Max; Bohner, Marc; Villanova, Julie
Abstract : This work evaluates the impact of experimental conditions on image quality when performing synchrotron X‐ray in‐line phase contrast nano‐tomography on mineralized biomaterials. For this purpose, a computational procedure to investigate signal‐to‐noise ratio and spatial resolution is proposed. Abstract : X‐ray nano‐tomography with phase contrast (nanoCT) using synchrotron radiation is a powerful tool to non‐destructively investigate 3D material properties at the nanoscale. In large bone lesions, such as severe bone fractures, bone cancer or other diseases, bone grafts substituting the lost bone might be necessary. Such grafts can be of biological origin or be composed of a synthetic bone substitute. The long‐term functioning of artificial bone substitutes depends on many factors. Synchrotron nanoCT imaging has great potential to contribute to further the understanding of integration of implants into bone tissue by imaging the spatial interaction between bone tissue and implant, and by accessing the interface between implant material and bone tissue. With this aim, a methodology for evaluating the image quality is presented for in‐line phase contrast nanoCT images of bone scaffold samples. A PMMA‐embedded tricalcium phosphate scaffold was used with both a closed and an open porosity structure and bone ingrowths as a representative system of three known materials. Parameters such as spatial resolution and signal‐to‐noise ratio were extracted and used to explore and quantitatively compare the effects of implementation choices in the imaging setup, such as camera technology and imaging energy, on the resulting image quality. Increasing the X‐ray energy from 17.5 keV to 29.6 keV leads to a notable improvement in image quality regardless of the camera technology used, with the two tested camera setups performing at a comparable level when the recorded intensity was kept constant.